Strategi Pemasaran Produk Fashion dengan Menggunakan TikTok Affiliate - Mufatikhatun Risqiyanti; Mohamad Maftuh Fauzi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
TikTok Affiliate is a sales method by promoting a brand's product and then receiving a commission on the sales generated. The purpose of this research is to find out how to market fashion products using TikTok Affiliate. The findings of this study are expected to provide an insight into marketing strategies using TikTok Affiliate. The results of this survey are likely to have practical implications that will help marketing practitioners develop effective strategies to address the challenges in digital marketing, with the ultimate goal of increasing purchases of fashion products.